CARBONATITES AND KAMAFUGITES IN ITALY: MANTLE-DERIVED ROCKS THAT CHALLENGE SUBDUCTION - Lavecchia G.; Stoppa F.; Creati N. (My University, 2006)
The carbonatite and kamafugite (i.e. potassic melilitite) rock-types of the Intramontane Ultra-alkaline Province (IUP, Italy) form a geologically rare, albeit not unique, ultramafic association. Their composition is in the range of other kamafugites and carbonatites, especially extrusive carbonatites, in the world (Katwe-Kikorongo and Bunyaruguru in Uganda, Oldoinyo Lengai in Tanzania and Quinling in Gansu, Central China). The kamafugite-carbonatite rock association requires specific tectonic-magmatic prerequirements: 1) metasomatised mantle source (enriched carbonate/phlogopite-bearing peridotite); 2) magma rapid rise to the surface to preserve a near primary state, to carry large mantle nodules and to limit the interaction with the crustal rocks and/or fluids; 3) geometry of the lithosphere suitable to favour the intersection of the local geotherm with the metasomatised peridotite solidus and to allow only very small-degrees of partial melting. The Italian kamafugite carbonatite geochemistry encompasses high LILE (Cs, Rb, K, Ba), high Sr-group (Sr plus REE), high LREE/HREE, high incompatible elements (Cr-Ni), but negative Eu anomaly, low light-HFSE4+ (Zr-Ti) and intermediate heavy-HFSE (Hf-Ta). This distribution requires a high CO2 fugacity in the source able to fractionate the HFSE and to produce the Eu anomaly. Based on geochemical criteria used for basaltic rocks, the IUP rocks were attributed by some authors to a subduction geodynamic setting, a fact which produced a catastrophic misunderstanding of these rocks. Worldwide kamafugites and carbonatites occur in intraplate and continental rift settings, the magmatogenetic conditions required for their genesis being unsuitable in a subduction environment, which is instead the dominating model for Italian volcanism. This consideration stimulated this review of the IUP field relationships, mineralogy, petrology and geochemistry. The IUP is sited about 50 km east of the large volcanoes of the Roman Co-magmatic Region (RCR). Plagioleucitites which are typical of the RCR, are also geologically rare and, when regionally associated with carbonatites and kamafugites, form a regional triad very typical of continental rifts. This triad has never been observed in subduction related environments, that are dominanted by large volumes of andesites and dacites. It may be better explained in the frame of a plume model that links the metasomatic process of the IUP mantle source with hydroxyl-CO2 rich radiogenic fluids and volatiles released within the Mediterranean asthenosphere from a plume head trapped in the transition zone (between the 410 and 670 km discontinuities).